The Relationship between Plasma Glutamate Levels and Sleep Quality in HIV Patients - Syofiadi, Dhiang Mulia; Yuliarni Syafrita; Lydia Susanti (HM Publisher, 2023)
Background: Disturbance sleep quality is often found in sufferers of human immunodeficiency virus (HIV). Disturbed sleep quality can affect immunity, which ultimately can increase patient morbidity and mortality. Impaired sleep quality in HIV sufferers is related to neurotoxicity due to the HIV virus, which damages sleep architecture. HIV infection can cause an increase in brain extracellular glutamate. Elevated glutamate plays a role in neuronal and glial damage and death. This study aimed to assess the relationship between plasma glutamate levels and sleep quality in HIV sufferers. Methods: The research uses a cross-sectional design. The samples were HIV sufferers in a polyclinic voluntary counseling test (VCT) internal medicine of Dr. M. Djamil General Hospital Padang, who met the inclusion and exclusion criteria. Samples are selected by consecutive methods. Sleep quality was assessed using a questionnaire called the Pittsburgh sleep quality index (PSQI). Plasma glutamate levels were measured using the ELISA method. Statistical analysis using SPSS with a p-value <0.05 was considered statistically significant. Results: The research sample consisted of 82 people. The median plasma glutamate level was 16.39 µg/mL. Impaired sleep quality was found in 45 (54.9%) HIV sufferers. There was no significant relationship between plasma glutamate levels (p= 0.506), age (p=0.795), gender (p=0.547), education (p=0.358), occupation (p=0.255), disease duration (p=0.348), stage (p=0.309) and type of ARV therapy (p=0.791) with sleep quality in HIV sufferers. From this research, a significant relationship was found between sleep quality, body mass index (BMI) (p= 0.015), and marital status (p= 0.039). Conclusion: There is no relationship between plasma glutamate levels and sleep quality in HIV sufferers. There are other factors that influence sleep quality, namely BMI and marital status.